EFEKTIFITAS PENGGUNAAN MEDIA DARING DALAM E-LEARNING - Siti Norhidayah (MECHA JURNAL TEKNIK MESIN, 2021)
The Corona Virus pandemic that entered the territory of Indonesia in early 2020 greatly affected the stability of all aspects of life, both in terms of the economy, industry and the education sector. The spread of this virus is growing exponentially rapidly throughout the world, including Indonesia, which ultimately the World Health Organization (WHO) declared that the Covid-19 outbreak was a world pandemic. Since the government through the Ministry of Education and Culture has issued circular number 4 of 2020 concerning the implementation of education policies during the emergency period of the spread of Covid-19, to support this government policy all lecture activities are automatically transferred online. The shift of the lecture method from face-to-face lectures and students in real classes to face-to-face in virtual classes has caused many things to be reviewed. This study describes the effectiveness of using online media during e-learning, its advantages and disadvantages and the obstacles that occur in using online media in the learning process. The research method used is descriptive research method. The technique of collecting data is through a questionnaire in the form of a google form which is distributed to odd semester students of the 2020/2021 Academic Year. Student responses contain statements in the form of indicators used to measure student activeness. The results showed that online learning was quite effective in the current Covid-19 pandemic. Student response to online learning is quite good. All learning materials provided by lecturers through e-learning can be absorbed well, although there are still shortcomings and obstacles in online learning that must be addressed. Keywords: Application, Microsoft Studio 2012, C #, Optical Character Recognition (OCR), EmguCV, Tesseract (Software), Document Archiving.